Reductions in Gastrointestinal Intolerance, Healthcare Resource Utilization and Cost Associated with a Plant-Based Peptide Enteral Formula with Fruit and Vegetable Ingredients: Retrospective Analysis of Children and Adults in Post-Acute Care - Minor G; Cekola P; Desai A; Kumar P; Mondal S; Kadam YV; Fazioli K; Klosterbuer A (Nutrition and Dietary Supplements, 2025)
Gerard Minor,1 Pamela Cekola,2 Amarsinh Desai,3 Pradeep Kumar,4 Sayan Mondal,4 Yashashree Vijay Kadam,4 Katherine Fazioli,4 Abby Klosterbuer2 1Pediatric Gastroenterology Hepatology and Nutrition, KIDZ Medical Services, Hollywood, FL, USA; 2Medical Affairs, Nestlé Health Science, Bridgewater, NJ, USA; 3Market Access, Nestlé Health Science, Bridgewater, NJ, USA; 4Life Sciences & Healthcare, Clarivate Analytics, Toronto, ON, CanadaCorrespondence: Pamela Cekola, Nestlé Health Science, 1007 US Highway 202/206, Bridgewater, NJ, 08807, USA, Email pamela.cekola@us.nestle.comPurpose: Peptide-based enteral nutrition (EN) formulas are an alternative to standard EN formulas for patients with gastrointestinal (GI) intolerance. Evidence supports GI tolerance benefits of either peptide-based EN or EN containing fruits and vegetables. However, there is a lack of research on plant-based peptide EN with added fruit and vegetable ingredients.Patients and Methods: This retrospective study analyzed United States (US) claims data on children (1– 13 years) and adults (≥ 14 years) receiving plant-based peptide formulas with fruit and vegetable ingredients in post-acute care. Demographics, GI tolerance, healthcare resource utilization (HCRU) and costs were captured. Clinical and health economic outcomes were compared 6 months pre-index and 1-, 3- and 6-months post-index in both cohorts.Results: In total, data from 91 children and 82 adults were analyzed. Mean (standard deviation [SD]) age was 5.5 (3.0) years in children and 49.0 (20.5) years in adults. Significantly fewer children and adults experienced any GI intolerance symptoms at all post-index time points compared with pre-index (p< 0.001). Significant reductions in individual GI symptoms including constipation, diarrhea, nausea and vomiting were observed in children and adults at all post-index time points compared with pre-index (p< 0.05). Significantly lower adjusted HCRU costs for inpatient and outpatient visits were reported at all post-index time points compared with pre-index for children. For adults, significant reductions in adjusted costs were reported for emergency, inpatient, outpatient, and urgent care at all post-index time points when compared with pre-index. Total adjusted costs were significantly reduced from $473,857 at pre-index to $273,134 at 3 months post-index (p< 0.05) for children, and from $676,456 at pre-index to $427,576 at 6 months post-index (p< 0.001) for adults.Conclusion: Children and adults prescribed plant-based peptide formulas with fruit and vegetable ingredients showed significant reductions in GI intolerance symptoms, HCRU and associated costs post-hospital discharge.Keywords: pediatric nutrition, peptide tube feeding, healthcare resource utilization, real food enteral formulas, intolerance, real-world evidence